Optimizing the Role of Regional Libraries Through the Kuningan Bercahaya Program in Improving Literacy Among the Community in Kuningan Regency - Nurghariza Ainunnisa; Kismartini Kismartini (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Libraries are public facilities that serve to maintain literacy among the general public. In Kuningan Regency itself, there is a special program to improve community literacy called Kuningan Bercahaya, which stands for Kuningan Belajar dan Membaca Sepanjang Hayat (Kuningan Learning and Reading Throughout Life). This study aims to analyze how the program is implemented and how the Regional Library plays a role as the authority in improving community literacy in Kuningan Regency. The research method used in this study is a descriptive qualitative approach. The research results were analyzed using the policy implementation theory dimensions, which include program implementation, community involvement, and implementation performance. To analyze the role, the facilitative role from the role theory of Jim Ife and Frank Tesoriero was used. The results showed that the program implementation was not yet optimal due to the absence of standard guidelines, limited resources, and weak coordination between agencies. However, the Regional Library has carried out most of its facilitative role, especially in the aspects of social animation, mediation, and support provision. Supporting factors came from community support and local government commitment, while inhibiting factors included a lack of budget, limited access to digital literacy, and unclear policy content.